INTERVENSI KESEHATAN BERBASIS KOMUNITAS: PENDEKATAN PKMD DI NAGARAKASIH KOTA TASIKMALAYA - Khusnul, Khusnul; Meri, Meri; Rahayu, Restu; Nisrina Zahrani, Marsha; Anisa Komariah, Tri; Nurfaqih, Fahmi; Maharani Agustin, Resti; Dhiya Wahyu, Faiq; Hanifah, Salwa; Budining Ayu, Anggia; Nazwa, Nazwa; Janah, Apridatul; Firdaus, Raihan; Lindiani, Dian (Universitas Bakti Tunas Husada, 2025)
The Village Community Health Development Program (PKMD) is a participatory approach aimed at improving public health awareness through promotive and preventive interventions. This program was implemented in RT 001/RW 002 Nagarakasih, Kersanegara Subdistrict, Cibeureum District, Tasikmalaya City, focusing on health education and basic health screening. The methods included initial surveys, health education sessions, medical examinations (blood pressure, blood glucose, cholesterol, uric acid, hemoglobin, and blood type), and descriptive data analysis. The results showed that 37.5% of participants had high blood pressure, 32.5% had elevated cholesterol, 17.5% had high uric acid levels, 17.5% had low hemoglobin levels, and 7.5% experienced hyperglycemia. Additionally, 32.5% of respondents did not know their blood type. Educational sessions on hypertension, presbyopia, and sanitation were found to improve residents’ understanding of healthy lifestyles. This activity demonstrated that PKMD is effective in increasing health literacy and community awareness regarding non-communicable disease prevention.